Evaluasi Galur Kedelai Transgenik Toleran Aluminium pada Fasilitas Uji Terbatas - Pardal, Saptowo J.; Suharsono, Suharsono (Pusat Penelitian dan Pengembangan Tanaman Pangan, 2016)
Some acid soil is potential for the agricultural development. Constraints for soybean production in the acid soils are Aluminum toxicity and macro nutrient deficiencies. Breeding for soybean varieties tolerant to acid soil is needed. This could be made through genetic engineering, by inserting acid tolerance genes into a soybean genome. Thirty one soybean lines (T0) had been obtained by insertion of Al tolerance genes (MaMt2) through an Agrobacterium mediated transformation, which nine of them contained MaMt2 gene based on PCR test. Further evaluation of those lines was carried out in the Biosafety Containment, where four T1 soybean lines were carrying MaMt2 gene, namely line GM2, GM5, GM10 and GM14. The study was aimed to evaluate the degree of tolerance of T2 generation of GM2, GM5, GM10 and GM14 lines to Al toxicity. Results showed that T2 line were able to grow in hygromicin media, indicating that those T2 lines were containing hygromicin resistant gene (hptII). Phenotypic analysis of T2 lines in four acid soil media treatments indicated that all lines could survive and grow on acid soil without liming and adding compost. GM2 line grew best on the acid medium than did other lines.